The Comisarias of the Holy Office in the Audience of Philippines. Conflict and Communications in a Peripheric Inquisitorial Space, 1583-1784 - Miranda Ojeda, Pedro (2021)
The enormous geographical distances and slowness in communications between Mexico and the Philippines constituted a problem in the provision of trades. The Tribunal of the Holy Office of New Spain, on whom they depended on to carry out an effective inquisitorial activity, had to implement a series of actions with the aim of correcting all these inconveniences, Mexico’s inquisitorial court implemented a series of measures. The first was to grant a special concession to the Manila comisaria to be able to apply sentences in minor crimes. The second was to establish a territorial division of the diocesan comisarias to expand their presence to most of the populations of the islands. Finally, the simultaneous appointment of three comisarios who could replace the owner at any time in case of absence.